Strategy for Strengthening the Professional Competency of Islamic Religious Education Teachers in Facing the Society 5.0 Era at Al Azhar 17 Galuh Mas Karawang Islamic High School - Nia Karnia; Nur Rochimah; Ilham Fahmi; Fadli Rais; Rifalda Nur Ziyada; Yustiara Hafipah (al-Afkar, Journal For Islamic Studies, 2025)
The strategy to strengthen the professional competence of Islamic Education teachers in facing the Society 5.0 era at SMA Islam Al Azhar 17 Galuh Mas Karawang is of utmost importance where education today has advanced significantly in line with the times. As agents of change, teachers must possess sufficient competence to face the challenges of the times in order to educate students in accordance with their era. This study is a field research using a qualitative approach involving the school principal as the quality management implementer and Islamic Education teachers as policy implementers. In this study, the researcher conducted observations and interviews with the school principal and Islamic Education teachers, and documented supporting data for the research. The challenges faced by Islamic Education teachers in facing the Society 5.0 era at SMA Islam Al Azhar 17 Galuh Mas Karawang include the need for teachers to instill character in students, impart the importance of seeking knowledge, address adolescent delinquency, develop personal skills and scholarly competence, adeptly conduct teaching and learning processes, create students who are proficient in communication, critical thinking, collaboration, problem-solving, and creativity. Competencies that teachers need to possess to confront the Society 5.0 era include pedagogical, personal, social, professional, spiritual, and leadership competencies. The school strives to enhance the professional competencies of Islamic Education teachers by providing supportive facilities, organizing various training or mentoring sessions to empower the roles of Teacher Working Groups (KKG) and Subject Area Teacher Professional Development Groups (MGMP), improving career systems and rewards, facilitating continuous professional development opportunities for teachers, and conducting benchmarking studies.